Isolation and Identification of Pathogenic Escherichia coli, Klebsiella spp. and Staphylococcus spp. in Raw Milk Samples Collected from Different Areas of Dhaka City, Bangladesh - Uddin, Md Aftab; Motazzim-ul-Haque, Hasan Md; Noor, Rashed (Stamford Journal of Microbiology, 2011)
The present study was undertaken with the aim of investigating the bacteriological quality of locally available raw milk. A total number of 22 raw milk samples were collected from Dhaka city and its surrounding areas during the period from October 2009 to November 2009. The analysis comprised enumeration of total viable bacterial count (TVBC), total coliform count (TCC) and total staphylococcal count (TSC) for the determination of sanitary quality. The highest TVBC, TCC and TSC were 2.36 x109 cfu/ml, 2.0 x 108 cfu/ml & 4.7 x 107 cfu/ml, respectively. In order to observe the antibiotic-resistance pattern, the antibiogram assay was carried out. All Escherichia coli isolated from raw milk exhibited 100% resistance against Rifampin (R) and Tetracycline (TE) and 50% resistance against Nalidixic Acid (NA) but were 100% sensitive against Imipenem (IPM). Klebsiella spp. exhibited 100% sensitivity against Imipenem (IPM). Staphylococcus spp. isolated from raw milk exhibited 100% resistance against Rifampin (R) and Nalidixic Acid (NA), but were 100% sensitive to Gentamicin (CN) and Imipenem (IPM). This survey indicates that most of the raw milk samples were not satisfactory in course of public health standard as some pathogenic bacteria were detected from these samples. Frequent use of antibiotics should be prohibited since antibiotic resistant strains are continuously increasing. DOI: http://dx.doi.org/10.3329/sjm.v1i1.9098 Stamford Journal of Microbiology, Vol.1(1), July 2011, p.19-23